JoJo's bizarre adventure. Part 6, Stone ocean. Volume 2 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2024)
"Stone Ocean is here! The highly acclaimed sixth arc of Hirohiko Araki's JoJo's Bizarre Adventure shifts the action from Italy to America, as Jolyne Cujoh--daughter of Jotaro Kujo--is sentenced to 15 years in prison for a murder she didn't commit! In a bizarre turn of events, the prison is filled with Stand users. Some become her allies, but many are sent to kill Jolyne and her friends in a scheme to resurrect the scourge of the Joestar family--DIO! It's a battle for survival in a prison where death lurks around every corner while Jolyne fights to save her father's life."--Publisher.